Cara Mengendalikan Penyakit pada Tanaman Jeruk Lemon (Citrus Limon) yang Dilakukan Oleh Petani di Tanjung Pering, Ogan Ilir, Sumatera Selatan - Sinaga, Anggiat Maruba; Enjeli Sihombing, Elma; Raihan, Muhammad; Prima, M Windra; Nurlaila, Nurlaila; Sagita, Sagita (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Sinaga AM, Sihombing EE, Raihan M, Prima MW, Nurlaila N, Sagita S. 2022. How to control in citrus limon plants performed by farmers in Tanjung Pering, Ogan Ilir, South Sumatera. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 318-326. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Oranges are the fruit of the annual plant of various citrus species in the family Rutaceae. Citrus plants, of course, have problems with growth, one of which is disease. The purpose of the survey is to find out what symptoms and diseases exist in citrus plants and find out how farmers control plants that are attacked by diseases in Tanjung Pering, North Indralaya District, Ogan Ilir Regency, South Sumatra. The research was conducted using a field survey method directly by collecting photos of citrus plants that were attacked by the disease, conducting interviews with farmers directly. Synthetic control is a way of controlling disease by citrus farmers in Tanjung Pering. Spraying by farmers is not done on a scheduled basis. Pesticide spraying activities are only carried out when many diseases and pests threaten agricultural activities. In controlling disease in citrus plants, biological and chemical control are carried out. Disease control in citrus plants should be done by means of biological control.